THE CONCEPT OF LEXICOLOGY AND ITS TRANSLATION - Ismatilloyeva Sokina Zarifboy qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Lexicology is the branch of linguistics that studies the nature, meaning, and function of words.  This field encompasses various aspects, including semantics, morphology, and etymology, ultimately aiming to understand how vocabulary reflects cultural and social contexts. Translating lexicological concepts requires careful consideration of meaning and usage across languages, highlighting the nuances that can influence interpretation. An effective translation not only conveys the original term but also maintains its cultural significance, making lexicology essential for both linguistic analysis and effective communication.